KESEPAKATAN PENIADAAN JAMINAN PENGADAAN DALAM KONTRAK PENGADAAN BARANG (STUDI KASUS PT. W DENGAN PT. A) - Yos Kelvin (Universitas Harapan Medan, 2020)
Goods/service procurement involves some parties and In this case, the procurement is made by PT. A As the users, and PT. W acts as the provider. Two of the most frequently guarantee practice said to be same yet not similar are Surety Bond and Guarantee Banks. This thesis is a combination of qualitative empirical research and statute approach with goods/service procurement as its object. The data are sourced from analysis of clauses in the contract based on interviews with respondents. Goods/service procurement guarantee is the accidental element that has to be firmly agreed by all parties. It supports the efficiency of the procurement in order to reduce the risk for default by provider in completing its obligation until the end date of contract period. Effectiveness will be achieved when all parties comply with the provisions of guarantee in line with its procedures and obligations stipulated in the Presidential regulation No. 16/2018 on Government Goods/Service Procurement. The absence of guarantee statement in the clauses may trigger tendency of criminal act of corruption among irresponsible parties thus, potentially detrimental to the country's finances. Whereas, there are sanction imposed, according to Article 97 in the Law No. 40/2007 on Limited Liability Companies, the directors who signed the contract are obliged to be liable for the mistake.